1992
DOI: 10.1002/dev.420250103
|View full text |Cite
|
Sign up to set email alerts
|

Contextual determinants of auditory learning in bobwhite quail embryos and hatchlings

Abstract: This study examined the ability of bobwhite quail embryos and hatchlings to learn an individual bobwhite maternal call. Results revealed that embryos could learn an individual maternal call and remember that call for at least 24 hr following exposure. In contrast, hatchlings reared socially in groups of same-age chicks during postnatal exposure to a maternal call did not demonstrate a preference for that familiar call at 24 hr following exposure. However, individual auditory recognition was exhibited by hatchl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
142
5

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 95 publications
(178 citation statements)
references
References 26 publications
31
142
5
Order By: Relevance
“…Chicks in the current study, in contrast, showed significant preferences for the familiar call with less than 5 min of exposure (or 29-45 repetitions on average) when that exposure was made contingent upon their own vocalizations. These results are particularly striking in that Lickliter and Hellewell (1992) found a preference for the familiar maternal call only when chicks were socially isolated following hatching. Foushée and Lickliter (2002), additionally, found a preference for the familiar call (with 240 min of exposure) only in chicks that were dark-reared during and following exposure.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Chicks in the current study, in contrast, showed significant preferences for the familiar call with less than 5 min of exposure (or 29-45 repetitions on average) when that exposure was made contingent upon their own vocalizations. These results are particularly striking in that Lickliter and Hellewell (1992) found a preference for the familiar maternal call only when chicks were socially isolated following hatching. Foushée and Lickliter (2002), additionally, found a preference for the familiar call (with 240 min of exposure) only in chicks that were dark-reared during and following exposure.…”
Section: Discussionmentioning
confidence: 89%
“…These were seen as unlikely possibilities given that socially reared chicks are frequently exposed to such vocalizations and because previous studies have found bobwhite chicks to have no naive preferences for either of these calls (e.g., Lickliter & Hellewell, 1992). It was nonetheless possible that the exposure to distress vocalizations might have had some influence on chick preferences.…”
Section: Experiments 2: the Effects Of Exposure To Conspecific Distresmentioning
confidence: 99%
See 1 more Smart Citation
“…36,46,47 Some species-specific range of normal exposure exists, and deviations of exogenous stimuli above or below this range, or with atypical timing, may negatively impact or alter typical perceptual development. 47,[48][49][50][51] Term newborns exposed to light with auditory pre-stimulation had a subsequent preference for lower light stimulation compared to babies who did not have increased auditory stimulation. 52 A similar study using incrementally increasing sound and light pre-stimulation, found a linear and inverse relationship.…”
Section: Processes Of Neurosensory Developmentmentioning
confidence: 99%
“…56,57 This postnatal bimodal exposure is facilitative, but if it occurs prenatally, or too early, it may have an 'interference effect' and lead to detrimental effects later in development. 33,50,58 Although intriguing and suggestive, these animal studies have not been established as predictive models for human brain development, and application of this research should be only in very general terms, recognizing interspecies variation. The normative ranges of acceptable sensory stimuli, as well as the exact impact of timing are not well defined in the human newborn.…”
Section: Processes Of Neurosensory Developmentmentioning
confidence: 99%